Global Findex Database 2017 : Measuring Financial Inclusion and the Fintech Revolution - Demirguc-Kunt, Asli; Klapper, Leora; Singer, Dorothe; Ansar, Saniya; Hess, Jake (Washington, DC: World Bank, 2018)
The Global Findex database is the world's most comprehensive set of data on how people make payments, save money, borrow and manage risk. Launched in 2011, it includes more than 100 financial inclusion indicators in a format allowing users to compare access to financial services among adults worldwide -- including by gender, age and household income.